Back Cover: Thermodriven Micrometer‐Scale Aqueous‐Phase Separation of Amphiphilic Oligoethylene Glycol Analogues (Chem. Asian J. 10/2014). Issue 10 (October 2014) - Kawasaki, Shunichi; Muraoka, Takahiro; Obara, Haruki; Ishii, Takerou; Hamada, Tsutomu; Kinbara, Kazushi
<x xml:space="preserve">Abstract</x> Amphiphiles Monodisperse oligoethylene glycol amphiphiles bearing aromatic units that exhibit a lower critical solution temperature (LCST) in water have been developed by Takahiro Muraoka, Kazushi Kinbara et al. In their Full Paper on page 2778 ff., they report their observation of concentration‐dependent hysteretic transmittance changes of the amphiphiles in response to temperature elevation and reduction. Dynamic light scattering measurements and phase contrast microscopy displayed the formation of micrometer‐size aggregates by heating at concentrations above 5.0 mM. These aggregates self‐assemble to form larger aggregates upon cooling before dissolution.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>